The Conceptual Metaphor of Cell for Ethics - Abdollah Salavati (Journal of Philosophical Investigations, 2021)
Metaphors in the new approach allow us to better understand ethics and bioethics due to their inherent capacities, such as highlighting and diversifying scripts from source domains. According to some, metaphors are not limited to conventional metaphors, not merely epistemological, but we need complex and unconventional metaphors for deep thinking and thoughtful cultural considerations. Stem cells, on the other hand, have extraordinary properties for the source domain in the unconventional and complex moral metaphor. Hence, the author has used the conceptual metaphor of cell for ethics. The fundamental question of this quest is: What aspects of morality does the conceptual metaphor of cell in ethics highlight for us? The findings of this study are as follows: 1. The conceptual metaphor of cell for ethics, unlike most ethical metaphors that are simple and common metaphors and naturally have less power for ethics, is a powerful, unconventional and complex metaphor and can handle ethical analysis well; 2. The metaphor mentioned in ethics is formed by moral phenomena and recognizes the distinction between religion and mysticism; 3. In the light of the cellular metaphor of ethics, the difference between ethical performance in different moral situations and ethical agents is better explained; 4. This metaphor, unlike other metaphors, highlights the idiosyncrasy of ethics, not a feature or few ethical features.